Boutique Hotel: the royal press / Fatin 'Aisyah Rosli ... [etal.] - Rosli, Fatin 'Aisyah; Ahmad Noorhani, Nur Maizura; Mustapha, Arniatul Aiza; Abd Rahman, Nur Adilla (College of Built Environment, 2023)
With the continuous advancement o science and technology, the modern printing process has been simplified, and only a computer and a printer can easily print articles or pictures , so the previous printing technology has been eliminate by the times.